Pengaruh Pembelajaran Online Kontekstual dengan Video Praktik Terhadap Pemahaman Materi Pengukuran bagi Peserta Didik - Maghfira Febriana; Harya Fitra Sahal Sasmita (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to determine the effect of applying contextual model online learning with practice videos on the understanding of the material for measuring Physics subjects for 10th grade MIPA at SMA Kesatrian 2 Semarang. The data was taken based on the results of the students' pretest and posttest and then analyzed using Wilcoxon non-parametric statistics. The hypothesis given is Ha: there is a difference in the results of the pretest and posttest, and Ho: there is no difference in the results of the pretest and posttest. Based on the SPSS calculation results show the value of asymp.sig. (2-tailed) = 0.000 with a significance level of 5% (0.05) because the value of 0.000 is smaller than 0.05, it is concluded that